2000
DOI: 10.1021/ac000061f
|View full text |Cite
|
Sign up to set email alerts
|

A Mass Spectrometry Method for the Determination of Enantiomeric Excess in Mixtures of d,l-Amino Acids

Abstract: A mass spectrometry method based on ion/molecule reactions for determining enantiomeric excess in mixtures of amino acids is illustrated. Protonated complexes of amino acids with beta-cyclodextrin are produced in the gas phase using electrospray ionization. Under a background pressure of N-propylamine, the amino acid is replaced by the alkylamine. The rates of the guest exchange reaction vary with the chirality of the amino acid. A calibration curve employing varying mixtures of D- and L-amino acids is produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
80
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 51 publications
(70 reference statements)
0
80
0
Order By: Relevance
“…Using this reaction, we probed the structure of gas-phase complexes [16,18,19] and determined enantiomeric excess of amino acids and pharmaceutical compounds [14,20,21]. Subsequently, other gas-phase methods have been used for determining enantiospecificity [22].…”
mentioning
confidence: 99%
“…Using this reaction, we probed the structure of gas-phase complexes [16,18,19] and determined enantiomeric excess of amino acids and pharmaceutical compounds [14,20,21]. Subsequently, other gas-phase methods have been used for determining enantiospecificity [22].…”
mentioning
confidence: 99%
“…This approach [26] comprises the use of the Relative intensity I r of the complex as a response of the complexed concentration of G. I r is defined as follows: I r ϭ I c /I tot , where I tot ϭ I c ϩ I G . As Figure 6 indicates, the repeatability of the measurements is excellent for all samples.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that "false positives" inclusion complexes should be precluded by applying other techniques to prove the complex formation. Since then, different studies have been reported that evidenced the existence of gas-phase inclusion complexes involving methods such as collision-induced dissociation [15,18,22], blackbody induced radiation dissociation [23], heated capillary dissociation [24], and mainly by guest-exchange reactions in gas phase with a CD host sensitive to the chirality of the amino acid guest [20,25,26].…”
mentioning
confidence: 99%
“…For example, chiral recognition based on gasphase ion/molecule reactions has been investigated by several research groups [18 -25]. In work by Dearden et al [18,23,24] and Lebrilla et al [19,22,25], a chiral host was used to form diastereometric adducts with a chiral ligand in the solution phase. The adduct ions were then electrosprayed into the gas phase, and allowed to exchange the chiral ligand through ion/molecule reaction with a neutral gas.…”
mentioning
confidence: 99%
“…Chiral distinction was achieved based on the variation of the exchange rate with the chirality of the analyte incorporated into the adduct ion. Quantification of the amount of each enantiomer was accomplished through the utilization of a calibration curve of the apparent exchange equilibrium constant versus enantiomeric excess [24] or by generating a calibration curve after a constant reaction time between the abundance of the unexchanged reactant and the mole fraction of one enantiomer [25]. In addition, ion/ molecule reactions have also been successively used in the differentiation of diasteromeric species [26 -28].…”
mentioning
confidence: 99%